Neurovirulence of Usutu virus in human fetal organotypic brain slice cultures partially resembles Zika and West Nile virus - Eleanor M. Marshall; Ahmad S. Rashidi; Michiel van Gent; Barry Rockx; Georges M. G. M. Verjans (Scientific Reports, 2024)
Abstract Usutu (USUV), West Nile (WNV), and Zika virus (ZIKV) are neurotropic arthropod-borne viruses (arboviruses) that cause severe neurological disease in humans. However, USUV-associated neurological disease is rare, suggesting a block in entry to or infection of the brain. We determined the replication, cell tropism and neurovirulence of these arboviruses in human brain tissue using a well-characterized human fetal organotypic brain slice culture model. Furthermore, we assessed the efficacy of interferon-β and 2′C-methyl-cytidine, a synthetic nucleoside analogue, in restricting viral replication. All three arboviruses replicated within the brain slices, with WNV reaching the highest titers, and all primarily infected neuronal cells. USUV- and WNV-infected cells exhibited a shrunken morphology, not associated with detectable cell death. Pre-treatment with interferon-β inhibited replication of all arboviruses, while 2′C-methyl-cytidine reduced only USUV and ZIKV titers. Collectively, USUV can infect human brain tissue, showing similarities in tropism and neurovirulence as WNV and ZIKV. These data suggest that a blockade to infection of the human brain may not be the explanation for the low clinical incidence of USUV-associated neurological disease. However, USUV replicated more slowly and to lower titers than WNV, which could help to explain the reduced severity of neurological disease resulting from USUV infection.